2022
DOI: 10.1021/acs.langmuir.2c00577
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Induced Liquid Metal Droplet Bouncing

Abstract: Liquid metals, including eutectic gallium–indium (EGaIn), have been explored for various planar droplet operations, including droplet splitting and merging, promoting their use in emerging areas such as flexible electronics and soft robotics. However, three-dimensional (3D) droplet operations, including droplet bouncing, have mostly been limited to nonmetallic liquids or aqueous solutions. This is the first study of liquid metal droplet bouncing using continuous AC electrowetting through an analytical model, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…44 It is also being used in emerging application spaces such as microfluidic acoustic metamaterial. 45 Electrowettingbased manipulation also allows operations such as droplet generation, oscillation, 46,47 merging, 48 splitting, 49 bouncing, 50 and mixing. 51 Additionally, spontaneous charging of the droplet has also been utilized for droplet manipulation applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…44 It is also being used in emerging application spaces such as microfluidic acoustic metamaterial. 45 Electrowettingbased manipulation also allows operations such as droplet generation, oscillation, 46,47 merging, 48 splitting, 49 bouncing, 50 and mixing. 51 Additionally, spontaneous charging of the droplet has also been utilized for droplet manipulation applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although we have previously demonstrated the vertical jumping of functional magnetic LM droplets controlled using an electromagnet, 32 this approach only allows very short locomotion along the vertical direction due to the weak magnetic force and bulky experimental setups. Other groups also investigate the vertical jumping of LM droplets in an electrolyte controlled by electrochemical oxidation and reduction; 33,34 such a method only allows instant vertical movement without the ability to provide continuous and precise 3D actuation. Moreover, by employing an acid droplet and liquid metal, the spontaneous and steady rotation of droplets is achieved, 35,36 which provides a new route for the design of potential applications (e.g., micro-and nanodevices).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many techniques have been developed to modify the charge distribution. For instance, Zavabeti et al demonstrated that pH or ionic concentration gradients across a liquid metal droplet induce both deformation and surface Marangoni flow; 20 Liu et al proposed a magnetic actuation and realized the deformation and motion of the liquid metal droplet; 21 Tang et al introduced a simple approach to rapidly vary and tune the size of liquid metal microdroplets by controlling the interfacial tension of the metal using both electrochemistry and electrocapillarity by applying an electrical potential to the liquid metal stream; 22 Idrus-Saidi et al reduced the surface tension of the droplet to almost zero using a combination of electrocapillary and vacuum filtration; 23 He et al effectively lowered the surface tension of the liquid metal droplets by applying 1.5 V voltage, causing the liquid metal to transform from a drop to a wire in NaOH solution, and the live liquid metal wire deformed under a magnetic field; 24 successfully achieved liquid metal droplet bouncing using continuous AC electrowetting; 25 and Song et al demonstrated an electrochemical approach to induce jumping behavior in liquid metal droplets. 26 The "mercury beating heart (MBH)" phenomenon, a classic deformation process of a liquid metal droplet (LMD), has been studied by many researchers since the nineteenth century.…”
Section: ■ Introductionmentioning
confidence: 99%